Implementation of Character Education Strengthening in Public Vocational High School - Heny Subekti; Alinurdin Alinurdin (Journal of English Education, 2021)
Character education is best understood as part of a moral education, which deals with the development of positive character which is commonly called virtue. For this reason, this study analyzes the implementation of strengthening character education at Public Vocational High School (SMK Negeri) 1 Bojonggede through 3 basic approaches, namely: class, school and community. This study used a qualitative method with a case study approach and used a purposive technique with the help of key people in determining the participants. While the data collection method uses the method of interviews, observation and other supporting documents. The results showed that the implementation of character education that has been running at SMK Negeri 1 Bojonggede is good in its management. Its integration with the curriculum and other supporting tools is key in running this program. This occurs because the Character Education Strengthening (CES) system at SMK Negeri 1 Bojonggede has been well established and is able to be portrayed in several school programs, as evidenced by the existence of planning, compilation, supervision, and completeness of evaluation.